Modern Techniques and Methods in Engineering Education - فائق محمد سرحان; أسماء عبد الجبار هادي; هدى فرحان ابراهيم (Journal of Engineering and Sustainable Development, 2012)
Teaching methods have evolved significantly since the advent of computer, engineering education as a science mission benefited greatly from the techniques and styles that have been made to modern education. With the advent of the Internet appeared educational websites in various scientific fields. Engineering Science has received a large share of this new medium, because the websites Engineering is one of modern technologies in engineering education, but the Iraqi engineer standing in front of puzzled by this new technology not only to limitations in its use, but the lack of information easily. There are quite a number of engineers or even students in the engineering disciplines are not good at English language proficiency full, forcing them to search the World Wide Web using their mother tongue to face the sad reality of the Arab Engineering sites. In addition, despite the scarcity of these sites engineering, we find that interest in this type of sites is forgotten and ignored, despite the increasing number of engineers in Iraq, which may lead to late arrival of information engineering to this category of specialized, and therefore there was a lack or gap development in the human element leads to the non-sensor Iraqi engineer for each new to put on the world market and stand bewildered before the rapid progress in various fields, and the inability to develop himself to acquire advanced skills or project development works, which could lead to delays in production...